2013
DOI: 10.9795/bullgsj.64.305
|View full text |Cite
|
Sign up to set email alerts
|

Radiometric Dating of tephras from Pre-caldera and Caldera-forming stages, Towada volcano, Northeast Japan.

Abstract: Takashi Kudo and Makoto Kobayashi (2013) Radiometric Dating of tephras from Pre-caldera and Caldera-forming stages, Towada volcano, Northeast Japan. Bull. Geol. Surv. Japan, vol. 64,, 2 figs, 2 tables.Abstract: Towada volcano is an active volcano located in the northern part of the Northeast Japan arc. We carried out fission-track (FT) and AMS radiocarbon ( 14 C) dating of tephras from Towada and Hakkoda volcanoes to establish a detailed eruptive history during the Pre-caldera and Caldera-forming stages of To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…5). The stratigraphy at location 3 has been reported by Kudo and Kobayashi (2013). Glass shards in samples 302, 303, 402, and 403, obtained by this study (Fig.…”
Section: Towada-biscuit 2 Tephra (To-bp2) Erupted Fromsupporting
confidence: 73%
See 3 more Smart Citations
“…5). The stratigraphy at location 3 has been reported by Kudo and Kobayashi (2013). Glass shards in samples 302, 303, 402, and 403, obtained by this study (Fig.…”
Section: Towada-biscuit 2 Tephra (To-bp2) Erupted Fromsupporting
confidence: 73%
“…The heavy-mineral assemblage in samples 302, 303, 402 and 403 consisted of orthopyroxene. The eruption age of To-BP2 has been estimated to be slightly younger than 20.8-21.5 cal ky BP on the basis of the 14 C age of humic sediments just below To-BP2 (Kudo and Kobayashi, 2013).…”
Section: Towada-biscuit 2 Tephra (To-bp2) Erupted Frommentioning
confidence: 99%
See 2 more Smart Citations
“…1). WP has been used to establish Middle Pleistocene marine terrace chronology (Miyauchi, 1985(Miyauchi, , 1987Koike and Machida, 2001 ;Matsu'ura et al, 2014) and its reported ages scatter in a wide range, 280±50 ka (Kuwabara, 2007) and 230±50 ka (Kudo and Kobayashi, 2013) by fission-track method, and 160-200 ka (Miyachi, 1985) and 270 ka (Kudo et al, 2004) by stratigraphical evidences. Recently, WP has been estimated to correspond to mid marine isotopic stage (MIS) 7 (around 220 ka) by correlation with δ 18 O stratigraphy in deep-sea sediments (Chikyu C9001C cores) off Shimokita Peninsula (Matsu'ura et al, 2014).…”
Section: Introductionmentioning
confidence: 99%